Mapping the agricultural landscape typology of Nueva Ecija applying the photo elicitation method in visualising farmer's perception of rice fields - Castillo, Robert Jed Nathaniel C.; Darapisa, Charl Justine B. (Quezon City College of Architecture, University of the Philippines Diliman, 2022)
In Nueva Ecjia, the landscape identity is threatened by rapid urbanization and land conversion which sets out challenges in preserving the locals’ landscape identity. Landscape identity and visual perception harmonize the way humans view their surroundings; however, little is known on how identity is affected by one's visual perception and vice versa. This is a missed opportunity because visual perception constitutes up to 80 percent of human perception which can be used to better understand identities in the landscape. Hence, this research aims to integrate the visual perception of farmers in Nueva Ecija into typologies that can be used as digital representation of the province. Governed by the Levels of Landscape Cognition, the researcher performed focus group discussions among 60 pairs through photo elicitation methods. After the ethnographic and statistical correlation analysis, the researcher identified the main landscape domains through the local’s imageability, familiarity and associability to their landscape. In terms of imageability, results show that handtractor has the highest mean with 75 percent of the pairs putting them in their perceived landscape elements among the 60 pairs. These are followed by karyada (newly harvested grain) and halimaw (harvester) respectively with 71.67 percent and 70 percent of the respondents identifying the same elements. Meanwhile, familiarity in the landscape depicts water motor pump had the highest score of 82. Lastly, in terms of associability, the top three answers include farm machineries they use in the farm with handractor, water motor pump, and halimaw (harvester) ranking the first three with scores of 81, 76, and 69 respectively. These processes were replicated to carefully identify the landscape identity in palayan (rice fields), karsada (roads), patubig (water source), kabayanan (village) and other spaces. This study creates an important juncture to represent human perception into a digital landscape representation. The results of the study promise how to better integrate human perception into navigable media that can better represent locals' perception towards the landscape. In return, local understanding and knowledge can be preserved in a setting that serves as a record for the landscape as it gets subjected to change over time.
includes appendices.
Thesis (Bachelor of Landscape Architecture)--University of the Philippines Diliman
Keywords: Agricultural landscapes -- Nueva Ecija